Tropical forests are home to over half of the world's vertebrate species. Issue 1 (7th October 2021) - Pillay, Rajeev; Venter, Michelle; Aragon‐Osejo, Jose; González‐del‐Pliego, Pamela; Hansen, Andrew J; Watson, James EM; Venter, Oscar
Abstract : Tropical forests are renowned for their astonishing diversity of life, but the fundamental question of how many species occur in tropical forests remains unanswered. Using geographic range maps and data on species habitat associations, we determined that tropical forests harbor 62% of global terrestrial vertebrate species, more than twice the number found in any other terrestrial biome on Earth. Up to 29% of global vertebrate species are endemic to tropical forests, with more than 20% of these species at risk of extinction. Humid tropical forests (also known as tropical rainforests) and the Neotropics dominate as centers of species diversity, harboring more than 90% and nearly half of all tropical forest vertebrates, respectively. To maintain the biodiversity that underpins the ecosystem functions and services essential for human well‐being, we emphasize the critical importance of environmental policies aimed at reducing tropical deforestation and mitigating deleterious anthropogenic pressures on these imperiled ecosystems.